Philippine national bibliography 2006 - Philippines. The National Library (Manila National Library of the Philippines, 2007)
"Philippine National Bibliography (PNB) lists works published or printed in the Philippines by Filipino authors or about the Philippines even if published abroad. It is published quarterly and cumulated annually." -- CD-ROM leaflet.
Pt. I: Monographs 2006 -- pt. II: Theses and dissertations 2000-2005.
PDF format.
Keywords: Philippines -- Bibliography